Nieuwsbrief Homocentrum Brugge. (Brugge : Gewestelijk Opvangcentrum voor Alleenstaanden (G.O.C.a.), 1983)
Fonds Suzan Daniel (FSD)
Periodiciteit : maandelijks
Redactie : Beenhouwersstraat 5, 8000 Brugge ; vanaf (1991) Sint-Clarastraat 43, 8000 BruggeV.V. Nieuws van 't Klein Verschil
Nederlands
Periodiek